2011
DOI: 10.1016/j.cub.2011.10.022
|View full text |Cite|
|
Sign up to set email alerts
|

Wiring Economy and Volume Exclusion Determine Neuronal Placement in the Drosophila Brain

Abstract: Wiring economy has successfully explained the individual placement of neurons in simple nervous systems like that of Caenorhabditis elegans [1-3] and the locations of coarser structures like cortical areas in complex vertebrate brains [4]. However, it remains unclear whether wiring economy can explain the placement of individual neurons in brains larger than that of C. elegans. Indeed, given the greater number of neuronal interconnections in larger brains, simply minimizing the length of connections results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
234
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(247 citation statements)
references
References 34 publications
13
234
0
Order By: Relevance
“…Consistent with this the placement of components within nervous systems is close to a configuration that minimizes the volume of wire at various scales from individual neurons [64][65][66] to brain regions [67,68]. Perhaps the clearest example of this wiring economy is in the layout of the C. elegans nervous system, where the positions of neurons show a striking match to the wire length minimized structure [6,64].…”
Section: Wiring Economymentioning
confidence: 72%
See 2 more Smart Citations
“…Consistent with this the placement of components within nervous systems is close to a configuration that minimizes the volume of wire at various scales from individual neurons [64][65][66] to brain regions [67,68]. Perhaps the clearest example of this wiring economy is in the layout of the C. elegans nervous system, where the positions of neurons show a striking match to the wire length minimized structure [6,64].…”
Section: Wiring Economymentioning
confidence: 72%
“…Perhaps the clearest example of this wiring economy is in the layout of the C. elegans nervous system, where the positions of neurons show a striking match to the wire length minimized structure [6,64]. More recent studies have shown that, the positions of neurons within more complex neural networks in insects adhere to a wire length minimized layout when the volume of the components is considered (volume exclusion) [65]. It has also been suggested that wiring economy can explain the difference in the position of the soma in invertebrate and vertebrate neurons [66].…”
Section: Wiring Economymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using genetic methods for single-cell labeling have confirmed many of these cell types and newly identified others (8,9). For ∼60 cell types in two optic lobe subregions, the lamina and medulla, their synaptic connectivity has been revealed through serial-section electron microscopy (EM) (10)(11)(12)(13). Cell types that have arbors that span only one or a few medulla columns have been the easiest to characterize.…”
mentioning
confidence: 97%
“…Studies of microscale wiring patterns in Drosophila have demonstrated that the topology of specific subcircuits can be explained on the basis of wiring length minimization and volume exclusion, both mechanisms directed at the economical conservation of space (Rivera-Alba et al 2011). In a more recent electron microscopic study, Takemura et al (2013) reconstructed a microscale circuit comprising 379 neurons and 8637 synapses within the optic medulla, a structure involved in visual motion detection.…”
Section: Microscalementioning
confidence: 99%